Universalistic and Situational Imperatives in Strategic Planning Systems Design: A Canonical Analysis - Calingo, Luis Ma. R. (Philippine Management Review, 2016)
This study seeks to improve our understanding of the design characteristics of effective strategic planning systems.  Predictions drawn from two alternative models of systems design are tested with data from 54 business organizations.  The findings suggest that the systems design task entails the confluence of both universalistic (“one best way’) and situational (“contingency” or “fit) imperatives.